The semeic function of the suffix -cha and -itu/ita - Cisneros Ayala, Claudia (2022)
The purpose of the article is to identify the sematic function of the suffix -cha of the Quechua variety chanka and the suffixes -ita and -itu attached to both Quechua and Hispanic lexemes. For this purpose, the behavior of the particle is examined as a function of its attachment to lexical bases of different grammatical categories. The author, based on her experience as a teacher and Quechua speaker, as well as through a process of interpretative induction, elaborated morphological cards with words such as the following: wasicha "little house", sumaqcha "the pretty one", qipichay "to pack", hamunqacha "sure to come", qamcha "sure to be you". As a result of the analysis, it is concluded that the semic functions of -cha joined to Quechua bases and in linguistic contact indicate conjecture, substantivation, affection, temporal shortening and anger.